Experimental evaluation of the interfacial properties of carbon nanotube coated carbon fiber reinforced hybrid composites. Issue 10 (20th June 2014) - Aziz, Shazed; Rashid, Suraya Abdul; Rahmanian, Saeed; Salleh, Mohamad Amran
<x xml:space="preserve">Abstract</x> A floating catalyst chemical vapor deposition (CVD) unit was utilized to grow CNT onto the surface of carbon fiber (CF). The surface morphology of the resultant fibers, CNT population density and alignment pattern were found to be depended on the CNT growth temperature, growth time, and atmospheric conditions within the CVD chamber. In contrast to the neat‐CF reinforced composites, improved interfacial shear strength (IFSS) between CF and matrix were obtained when the surface of CF was coated by CNT. Particularly, CF treatment condition for CNT‐coating with 700°C reaction temperature and 30 min reaction time has shown a considerable increase in IFSS approximately of 45% over that of the untreated fiber from which it was processed. The proper justification of fiber–matrix adhesion featured by composite interfacial properties was explained through IFSS. POLYM. COMPOS., 36:1941–1950, 2015. © 2014 Society of Plastics Engineers